RISK MANAGEMENT ANALYSIS OF COFFEE DREGS BRISKET INNOVATION; ALTERNATIVE FUELS IN INDONESIA - Yudhaningsih, Anik; Syah, Tantri Yanuar Rahmat (MANAJEMEN DEWANTARA, 2024)
Risk management is an activity that combines risk recognition, risk assessment, the development of strategies to manage it, and risk mitigation using managerial resources. Some traditional approaches to risk management focus on risks arising from physical or legal causes (such as natural disasters or fires, accidents, or mortality). On the other hand, financial risk management focuses on hazards that can be managed using traded financial instruments. The objective of risk management is to reduce to an acceptable level the various hazards associated with a predetermined domain. It can refer to a variety of hazards posed by the environment, technology, people, organizations, and politics. This paper describes the various steps of the risk management process, identifies the methodologies used at each step, and provides examples of risk and safety management that is used at PT. Energia Kopi Kreasindo.